DEVELOPMENT OF ISLAMIC EDUCATION METHODS - Kusmianto Kusmianto; M. Syukri Azwar Lubis (Jurnal Bilqolam Pendidikan Islam, 2026)
Teaching methods in Islamic education have undergone significant changes over time. These changes aim to meet people’s need for knowledge and keep pace with the times, which demand balanced and continuous transformation. Given the various challenges currently facing the world of Islamic education, every effort to maintain a balance between traditional and modern values is essential. Within this context, educators strive to integrate aspects of modernization into the realm of Islamic education without abandoning its religious values. By leveraging the latest innovations, educators can address emerging challenges and provide a more relevant and meaningful educational experience for the younger generation. Therefore, it is crucial for educators to continuously adapt and develop teaching methods that align with the demands of the times, while steadfastly upholding the core values of Islamic education.